Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy in patients with liver involvement. Issue 4 (25th January 2016) - Berger, Yaniv; Aycart, Samantha; Tabrizian, Parissa; Agmon, Yahel; Mandeli, John; Heskel, Marina; Hiotis, Spiros; Sarpel, Umut; Labow, Daniel M.
Abstract : Background: We examined outcomes of patients undergoing cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) combined with liver resection. Methods: All patients undergoing CRS/HIPEC between 2007 and 2014 were retrospectively reviewed: patients who underwent synchronous liver resection (group 1) were compared with those who did not (group 2) in terms of perioperative and long‐term results. Results: Group 1 included 103 patients with colorectal cancer (CRC, n = 28), appendiceal cancer (n = 34), and other malignancies. Compared with group 2 (n = 166), group 1 had higher number of organs resected, increased intraoperative blood loss, and longer hospital stay (all P ≤ 0.004) but similar major morbidity (24.3% vs. 18.1%, P = 0.22) and perioperative mortality rates. Two patients from group 1 developed liver resection‐related complications. A comparison between patients who underwent parenchymal liver resection (n = 42) and matched pairs from group 2 with similar extent of cytoreduction did not yield significant differences in morbidity/mortality. CRC patients from group 1 had poorer median overall survival (45.1 vs. 73.5 months from stage IV diagnosis, P = 0.009). Conclusions: Liver involvement denotes high peritoneal carcinomatosis burden, which often requires resection of multiple organs in order to achieve optimal cytoreduction. However, liver resection‐related morbidity is low and overall morbidity/mortality rates are comparable to other extensive CRS/HIPEC procedures. J. Surg. Oncol. 2016;113:432–437 . © 2016 Wiley Periodicals, Inc.